2016
DOI: 10.1177/0363546516660979
|View full text |Cite
|
Sign up to set email alerts
|

Injuries to the Collateral Ligaments of the Metacarpophalangeal Joint of the Thumb, Including Simultaneous Combined Thumb Ulnar and Radial Collateral Ligament Injuries, in National Football League Athletes

Abstract: Simultaneous combined thumb UCL and RCL tear is a previously undescribed injury pattern that occurred in 25% of thumb MCP collateral ligament injuries on a single NFL team over a 23-year period. All players with combined thumb UCL/RCL injuries required surgical repair, which was significantly higher compared with players with isolated UCL injuries. Team physicians and hand surgeons treating elite football players with suspected thumb collateral ligament injuries should examine for RCL and UCL instability and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…If ignored, these collateral ligament injuries can lead to chronic pain, decreased pinch strength, instability and metacarpophalangeal joint (MCP) osteoarthritis 1 3. Simultaneous combined collateral ligament injuries of the thumb has been reported by Brian et al in adults involved in high-contact sports activities 4. Here, we present a case of 15-year-old boy with combined collateral ligament injury.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…If ignored, these collateral ligament injuries can lead to chronic pain, decreased pinch strength, instability and metacarpophalangeal joint (MCP) osteoarthritis 1 3. Simultaneous combined collateral ligament injuries of the thumb has been reported by Brian et al in adults involved in high-contact sports activities 4. Here, we present a case of 15-year-old boy with combined collateral ligament injury.…”
Section: Introductionmentioning
confidence: 55%
“…There is only one report of simultaneous tears of the radial and ulnar collateral ligaments of the MCP joint of the thumb seen to occur in professional athletes who participate in high-impact sports like rugby and National Football League. Such injuries are thought to occur as an acute event which involves a combination of rotation, axial loading, translation and hyperextension in addition to an abduction and/or adduction force 4. In our case, the boy had sustained both the ulnar and radial collateral ligament injuries while playing low-impact sports and following repeated cumulative trauma.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This text concluded that combined UCL and RCL ligamentous injuries in the National Football League were a frequently undescribed and underdiagnosed injury. 1 They proposed that any patient presenting with an isolated ligamentous injury should have the contralateral ligament assessed for injury. 1 If combined injuries are present, they should be treated with surgical intervention.…”
mentioning
confidence: 99%
“…1 They proposed that any patient presenting with an isolated ligamentous injury should have the contralateral ligament assessed for injury. 1 If combined injuries are present, they should be treated with surgical intervention. 1 Combined ligamentous injuries were also reported by Bhat et al, in which J Hand Microsurg:2020;12:133-134 Letter to the Editor an adolescent sustained two separate injuries while playing volleyball and badminton.…”
mentioning
confidence: 99%